ECONOMIC PROTECTION TOWARD FINANCIAL MANAGEMENT HAJJ FUNDS: INDONESIAN CASE - Muhammad Iqbal Fasa; Adib Fachri; Ghina Ulfah Saefurrohman; Ahmad Hazas Syarif; Suharto Suharto (Ad-Deenar: Jurnal Ekonomi dan Bisnis Islam, 2020)
The potential for Haj funds in Indonesia is enormous. However, the long queues to perform the Haj pilgrimage lasted up to 17 years. The state has not wholly-owned facilities for operational needs. This study offers a new model in the management of Hajj funds in Indonesia. The offer in this research is the formation of economic independence protection by developing business units such as accommodation facilities in Mecca and Medina, Hajj planes, tours and trips, catering, hajj and umrah equipment stores, convenience stores, Indonesian culinary specialties, convection, e-payment systems. Hajj, Bottled Drinking Water, Sukuk Investment, and Other Investments. All of the profits from these funds are turned back for capital and business unit development. Thus, all the benefits of the hajj fund will again be felt by the people of Indonesia.